Predictors of unsuccessful mobilization with granulocyte colony‐stimulating factor alone in patients undergoing autologous hematopoietic stem cell transplantation. Issue 4 (21st February 2013) - Chow, Signy; Lazo‐Langner, Alejandro; Ormond, George; Howson‐Jan, Kang; Xenocostas, Anargyros
<x xml:space="preserve">Abstract</x> Mobilization of hematopoietic stem cells is achieved with hematopoietic growth factors with or without chemotherapy or other agents. Although studies comparing granulocyte colony‐stimulating factor (G‐CSF) alone to combined regimens demonstrate an increase in stem cell yield in the latter, mobilization with G‐CSF alone is still effective and has been widely practiced. We conducted a retrospective cohort study of consecutive patients at our institution who underwent at least one mobilization attempt with G‐CSF between January 2000 and December 2008 to identify the proportion of patients failing one or more mobilization attempts and the potential predictors of mobilization failure with this regime. Out of 293 patients, 251 (86.6%) were successfully mobilized and 244 (83.6%) underwent hematopoietic stem cell transplantation. Median yield was 3.55 × 106 CD34+ cells/kg. On univariate analysis, mobilization success was influenced by degree of previous treatment and underlying diagnosis (P < 0.001 each) but not by age (P = 0.114), sex (P = 0.860), or radiotherapy (P = 0.454). A diagnosis of non‐Hodgkin's lymphoma (NHL) and number of previous chemotherapy regimens were predictors of failure on multivariate analysis. CD34+ yield was influenced by diagnosis and previous chemotherapy (P < 0.001 each). Mobilization with G‐CSF alone yields adequate collections for most patients; however, heavily pretreated NHL patients with one failed attempt had high rates of remobilization failure and should be considered for alternative regimens. J. Clin. Apheresis 28:285–292, 2013. © 2013 Wiley Periodicals, Inc.